Transcranial Direct Current Stimulation Modulates Human Color Discrimination in a Pathway-Specific Manner - Costa, Thiago Leiros; Nagy, Balázs V.; Barboni, Mirella T.; Boggio, Paulo S.; Ventura, Dora F. (Frontiers in Psychiatry, 2012)
Previous research showed that Transcranial Direct Current Stimulation (tDCS) can modulate visual cortex excitability. However, there is no experiment on the effects of tDCS on color perception to date. The present study aimed to investigate the effects of tDCS on color discrimination tasks. 15 healthy subjects (mean age of 25.6 ± 4.4 years) were tested with Cambridge Color Test 2.0 (Trivector and Ellipses protocols) and a Forced-choice Spatial Color Contrast Sensitivity task (vertical red-green sinusoidal grating) while receiving tDCS. Anodal, cathodal and sham tDCS were delivered at Oz for 22 minutes using two square electrodes (25cm2 with a current of 1.5mA) in sessions separated by 7 days. Anodal tDCS significantly increased tritan sensitivity (p<0.01) and had no significant effect on protan, deutan or red-green grating discrimination. The effects on the tritan discrimination returned to baseline after 15 minutes (p<0.01). Cathodal tDCS reduced the sensitivity in the deutan axis and increased sensitivity in the tritan axis (p<0.05). The lack of anodal tDCS effects in the protan, deutan and red-green grating sensitivities could be explained by a “ceiling effect” since adults in this age range tend to have optimal color discrimination performance for these hues. The differential effects of cathodal tDCS on tritan and deutan sensitivities and the absence of the proposed ceiling effects for the tritan axes might be explained by Parvocellular (P) and Koniocellular (K) systems with regard to their functional, physiological and anatomical differences. The results also support the existence of a systematic segregation of P and K color-coding cells in V1. Future research and possible clinical implications are discussed.